2020
DOI: 10.1016/j.jsbmb.2019.105501
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the intestine: Review and update

Abstract: The central role of vitamin D in calcium homeostasis is to increase calcium absorption from the intestine. This article describes the early work that served as the foundation for the initial model of vitamin D mediated calcium absorption. In addition, other research related to the role of vitamin D in the intestine, including those which have challenged the traditional model and the crucial role of specific calcium transport proteins, are reviewed. More recent work identifying novel targets of 1,25(OH) 2 D 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…1,25(OH) 2 D 3 action in vivo has been explored at different mechanistic levels in intestinal epithelia and in kidney cortex (enriched in proximal tubules). In intestinal epithelial cells isolated from mice pre-injected with 1,25(OH) 2 D 3 , the VDR is bound to multiple genes across the mouse genome; its binding is enhanced by prior treatment with 1,25(OH) 2 D 3 [100][101][102]. More recent studies have revealed differences in VDR binding in enterocytes vs. crypt cells, suggesting differential roles for vitamin D in these two cells [101,102].…”
Section: Recent Work At the Frontier For Enhancing Vitamin D Analogue Sar Potentialmentioning
confidence: 99%
“…1,25(OH) 2 D 3 action in vivo has been explored at different mechanistic levels in intestinal epithelia and in kidney cortex (enriched in proximal tubules). In intestinal epithelial cells isolated from mice pre-injected with 1,25(OH) 2 D 3 , the VDR is bound to multiple genes across the mouse genome; its binding is enhanced by prior treatment with 1,25(OH) 2 D 3 [100][101][102]. More recent studies have revealed differences in VDR binding in enterocytes vs. crypt cells, suggesting differential roles for vitamin D in these two cells [101,102].…”
Section: Recent Work At the Frontier For Enhancing Vitamin D Analogue Sar Potentialmentioning
confidence: 99%
“…In line with its physiological role in the intestine, promoting the absorption of calcium and phosphate, the intestinal epithelium barrier function and xenobiotic metabolism, 1,25(OH) 2 D 3 induces the differentiation of normal colon epithelial cells through the upregulation of many epithelial enzymes and markers and through maintaining the morphology typical of the epithelial differentiated phenotype [ 14 , 15 ]. Concordantly, in colon carcinoma cells 1,25(OH) 2 D 3 induces a change in morphology that increases cell–cell adhesion and cell flattening ( Figure 1 a), which is paralleled by a decrease in proliferation.…”
Section: Effects Of 125(oh) 2 D 3 mentioning
confidence: 99%
“…Dr. Wasserman's research on the identification, induction by vitamin D, and function of the intestinal and renal calcium binding proteins (calbindin D9k and D28k in mammals, respectively) served as a foundation for the facilitated diffusion model of transepithelial calcium transport. After her tribute, Dr. Christakos continued to give an invited talk that described new research on vitamin D signaling in the intestine [21]. He talk began with a review of her recent publication on the role of signaling through the VDR in the distal intestine.…”
Section: Overviewmentioning
confidence: 99%